Comparative Analysis of Mycoviral Curing Techniques for Evaluating Fungal Host Fitness - Sultan, Hafiz Muhammad; Ali, Taimoor; Zubair, Muhammad; Ashraf, Aneela; Sultan, Mohsin (University of Brawijaya, 2026)
The viruses that infect fungi are called mycoviruses, and they were initially discovered in mushrooms. The prevalence of new mycoviruses has increased due to breakthroughs in sequencing methods. As a result, publicly accessible genomic sources provide access to several mycoviral transcripts. Genomic information alone is insufficient for comprehending the impacts of mycoviruses on their host fungus. Mycovirus can have a variety of phenotypic impacts on its host. For biological characterization, there is a need to determine the nature of the mycovirus, which may be hypovirulent, hypervirulent, or cryptic. Mycoviruses best characteristics are biological control of fungi and therapeutic potential. Currently, there is no standard method used against the mycoviral infection. Given the importance of mycoviral curing, we may prepare the isogenic lines. Single-spore isolation generally yields high success rates and is recommended as a first-choice approach for most fungal; system for the preparation of isogenic lines. In order to obtain reliable results, the study of mycovirology should also employ modern bioinformatics techniques to anticipate virus-specific antiviral properties.